PENGARUH PROFITABILITAS DAN BIAYA OPERASIONAL TERHADAP PAJAK PENGHASILAN BADAN PADA PT MULTI BINTANG INDONESIA Tbk TAHUN 2012-2021 - Sembiring, Yan Christin Br; Sitanggang, Sridesi (UNIKA Santo Thomas, 2024)
This study aims to determine the Effect Of Profitability And Operating Costs On Corporate Income Tax At PT Multi Bintang Indonesia Tbk In 2012-2021. This study uses secondary data taken from the income statement of PT Multi Bintang Indonesia Tbk through the company's official website. The population used is the quarterly income statement in 2012-2021. The sampling method used in this study was purposive sampling method and 39 samples were obtained which became the object of research. The analysis method used is multiple linear regression equations using the SPSS program. From the test results using SPSS, it is known that the coefficient of determination (R Square) is 0.966 or 96.6%, which means that profitability and operating costs together affect corporate income tax by 96.6%. Based on the results of the t test, it can be concluded that (1) profitability has a positive and significant effect on corporate income tax at PT Multi Bintang Indonesia Tbk in 2012-2021. (2) operating costs have a positive and significant effect on corporate income tax at PT Multi Bintang Indonesia Tbk in 2012-2021. And based on the F test, it is concluded that profitability and operating costs simultaneously have a positive and significant effect on corporate income tax at PT Multi Bintang Indonesia Tbk in 2012-2021.